A clinical study to determine the relationship between serum vitamin D levels and severity of asthma - kumar, Pragalatha; Gowdra, Aruna; Arathi, Arathi; Sampath, Ananya (International Journal of Contemporary Pediatrics, 2017)
Background: Vitamin D deficiency has been rediscovered as a public health problem worldwide. Few studies have shown that vitamin D deficiency is associated with asthma severity. The objective of present work was to study the serum vitamin D levels and its relationship with asthma severity in children. Methods: A prospective cohort study of 100 children with asthma between the age group of 5 to 15 years and age and sex matched 40 healthy controls who had come to Indira Gandhi Institute of Child Health, Bengaluru was done. These children’s serum vitamin D levels were estimated and correlated with asthma severity. Results: A total of 100 children with asthma and 40 healthy age and sex matched controls were evaluated. The study group had lower vitamin D (34.95 ng/ml) levels as compared to the control group (57.94 ng/ml) which was statistically significant (p<0.05). 68.4% children had significantly low vitamin D levels and severe form of asthma (p value <0.001). There was also a marked rise in absolute eosinophil count in those who had low vitamin D levels (56.6%) (p-value <0.0001). Conclusions: Vitamin D deficiency is an important risk factor for asthma severity. It modifies the immune system and reduces the inflammation. In the present study, low serum vitamin D levels were significantly correlated with severe form of asthma. There was a significant rise in the absolute eosinophil count in those who exhibited deficiency of vitamin D.